Fertilizer quantity and type alter mycorrhizae‐conferred growth and resistance to herbivores. Issue 5 (3rd February 2021) - Getman‐Pickering, Zoe L.; Stack, George M.; Thaler, Jennifer S.
Abstract: Plants face a constant struggle to acquire nutrients and defend themselves against herbivores. Mycorrhizae are fungal mutualists that provide nutrients that can increase plant growth and alter resistance to herbivores. The beneficial effects of mycorrhizae for nutrient acquisition can depend on the quantity and type of soil nutrients available, with plants usually benefiting more in terms of growth from mycorrhizae when nutrients are limited. However, it is unclear how the addition of different nutrients might shift mycorrhizal‐conferred resistance to herbivores by changing defensive secondary chemistry and nutrient availability. We conducted two concurrent greenhouse experiments to test how three levels of fertilizers (low, medium and high) and three types of fertilizers (organic, organically derived and inorganic) altered mycorrhizae‐conferred resistance to herbivores in tomato plants. In addition, we looked at whether mycorrhizae‐conferred resistance was driven by plant secondary metabolites or the nutrient content of the leaves. Association with mycorrhizae was associated with an increase in biomass at low levels of fertilization and decreased biomass at high levels of fertilization. Interestingly, mycorrhizae increased resistance to herbivores at medium levels of fertilization, but had no effect at low and high levels of fertilization. Mycorrhizae improved resistance most strongly when plants were fertilized with a phosphorus rich, organically derived fertilizer. In both experiments, increased resistance was correlated with changes in the plant's foliar nitrogen content. Synthesis and applications . Our study supports the potential for mycorrhizae to improve either crop growth or pest resistance under lower fertilizer conditions. However, mycorrhizae did not provide both growth and resistance benefits under any treatment. While mycorrhizae have the potential to benefit crops in in lower input systems, it may be challenging to maximize both growth and resistance benefits. Abstract : Our study supports the potential for mycorrhizae to improve either crop growth or pest resistance under lower fertilizer conditions. However, mycorrhizae did not provide both growth and resistance benefits under any treatment. While mycorrhizae have the potential to benefit crops in in lower input systems, it may be challenging to maximize both growth and resistance benefits.